Laboratory Evaluation of Certain Essential Oils for Their Larvicidal Activity against Aedes Albopictus, Vector of Dengue and Chikungunya - Varun Tyagi; Ruchi Yadav; Vijay Veer (Global Journal of Zoology - Peertechz Publications, 2016)
Mosquito borne diseases including malaria, fi lariasis, dengue, chikungunya and various forms of encephalitis impose enormous menace to human as well as animals. These diseases cause large number of mortality and morbidity across the world. The principal strategy for combating these diseases is the vector control including the use of larvicide against the immature stages of mosquitoes. Use of essential oils as mosquito repellent has been recommended by various studies but their role as larvicide is studied by only a few workers. In the present study, we have evaluated certain essential oils namely; Amyris, Black pepper, Cinnamon, Dill, Jasmine, Juniper and Thyme oils, against Aedes albopictus for their larvicidal activity. These essential oils have shown signifi cant larvicidal activity. These oils were shown to have LC50 values in the range of 10.5 to 62.7 ppm against larvae Ae. albopictus. Out of these seven oils the Dill oil was found to show the least LC50 value against Ae. albopictus.